Collusion in a Bertrand duopoly model with decreasing returns and product differentiation - Contreras, Roberto (Estudios de Economía, 2016)
We study cartel stability in a differentiated price-setting duopoly with returns to scale. We show that a cartel may be equally stable in the presence of lower differentiation, provided that the decreasing returns parameter is high. In addition we demonstrate that for a given factor of discount, there are technologies that can have decreasing returns to scale where the cartel always is stable independent of the differentiation degree.